Characterizations of the longitudinal beam behaviors and impedances measurements at HLS-II. (January 2022) - Zhao, Yunkun; Wang, Jigang; Sun, Baogen; Wu, Fangfang; Zhou, Tianyu; Lu, Ping
Highlights: The longitudinal beam behaviors and bunch characteristics are investigated. The longitudinal impedances of HLS-II are measured by the proposed T-BCPE method. This T-BCPE method has practicability, feasibility and reliability. Abstract: In this article, the longitudinal beam bunch behaviors of the Hefei Light source-II (HLS-II) are effectively investigated and analyzed based on the beam multi-parameter measurement system. Simultaneously, the temporal beam characteristic parameter extraction (T-BCPE) method is developed for measuring the longitudinal impedances of machine. In the case of 100.4 kV radio-frequency (RF) voltage, the inductance and resistance in the longitudinal coupling impedance of HLS-II are obtained as 115 ± 13 nH and 1320 ± 310 Ω by extracting bunch lengthening factor and asymmetry factor, respectively. In addition, the longitudinal beam dynamical characteristics and potential-well distortion are also in-depth analyzed above the threshold current of the microwave instability. As a result, the longitudinal broadband impedance of HLS-II is measured to be 8.94 ± 0.44 Ω while 0.339 ± 0.004 of the scaling factor in combination with the theoretical analysis.